THE DIFFERENCES OF PROJECT-BASED LEARNING AND COOPERATIVE LEARNING MODELS TO INFLUENCE OF CRITICAL THINKING ABILITY IN STUDENT MEDICAL AND SURGICAL SUBJECT 3RD SEMESTER OF DIII NURSING STUDY PROGRAM - Binarti Dwi Wahyuningsih; Sri Sudarsih; Moh. Zainudin (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Achieve maximum academic competition, it is necessary to have critical thinking skills. Both of these are certainly influenced by the learning methods applied by lecturers. Learning of Medical Nursing Nursing learning requires cognitive, affective and psychomotor abilities. Learning methods that are appropriate and easily accepted by students such as project based methods learning and cooperative learning provide learning experiences in the classroom to think more critically and have a high ability to master the concepts and cause motivation to learn. The purpose of this study was to determine the differences in the effect of Project Based Learning learning methods with Cooperative Learning on motivation and Critical Thinking skills in Surgical Medical Nursing teaching. The source population in this study was student D III Nursing STIKES HEALTHY DEVELOPMENT PPNI Mojokerto Semester III. The sample in this study was the third semester students, Nursing Diploma Program, as many as 78 students. The data collection techniques of this research were written test and questionnaire test. Data analysis was performed with data normality test using Kolmogorov mSmirnov test and the results were all data were normally distributed so that the data analysis used different tests namely Mann Whitney, as well as to determine differences in the effect of each class using the Wilcoxon test. The results showed the Asymp.Sig (2tailed) < 0.05 which is 0.000 which means that there are differences in critical thinking skills between classes that use the project based learning model and the Cooperative Learning model after receiving treatment. The Project Based Learning Method guides students through a problem that is solved by a project so that the ability to think in students is more increased.